Genetic and ecological conservation issues for oceanic island birds, revealed by a combination of the latest molecular techniques and conventional field work. Issue 2 (8th January 2019) - Ando, Haruko
Abstract: Oceanic island ecosystems are vulnerable to artificial disturbances, and many island endemics are at risk of extinction. Conservation of island endemics is a high priority for reducing biodiversity loss, but fundamental studies on many species remain lacking due to the small population size and limited accessibility to island habitats. In this review, I explored conservation issues of endangered bird species in oceanic island habitat, which have been revealed by the latest molecular techniques with a combination of conventional field work. Recent genetic studies revealed low genetic diversity of endangered island endemics. Analyses of genetic structure have revealed the gene flow of endemic birds among islands according to their flying abilities. Seasonal inter‐island movement of Columbiformes and some finches have been observed, which might be related to fluctuating food resource availability among island habitats. Dietary analyses based on DNA metabarcoding for Columba janthina nitens revealed frequent consumption of introduced plants by this bird. This review may provide a new perspective for conservation biology in oceanic island ecosystems. That is, (a) appropriate management of genetic diversity within and outside of habitat before serious population declines occur, (b) detection of meaningful evolutionarily significant units (ESUs) considering flying ability of birds among islands and management of total habitat range within each ESU and (c) introduced species eradication designed to not to cause a negative impact on endangered species that may depend on introduced species for their food. Abstract : The latest molecular techniques and conventional field worksprovided new perspectives on species conservation on oceanic islands: 1) appropriate management of genetic diversity within and outside of habitats before serious population declines occur, 2) detection of meaningful ESUs considering flying abilities of birds among islands and management of total habitat ranges within each ESU, and 3) introduced species eradication designed to not to cause a negative impact on endangered species that may depend on introduced species for their food.